The Use of ICT by SME Shoe Crafters in Cibaduyut - Solihin, O; Mogot, Y; Rohmawati, T; Yasundari (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The era of information and communication technology (ICT) advancement has brought changes to various sectors of life. This study aims to analyze the utilization of ICT by shoe crafters in Cibaduyut, Bandung. A case study was conducted on several shoe crafters in Cibaduyut as small and medium-sized enterprises. Data collection methods included in-depth interviews and field observations. The results showed that the majority of shoe crafters in Cibaduyut have utilized ICT. For them, ICT provides benefits such as faster access to information, increased operational efficiency, improved competitiveness, and increased access to markets. The use of ICT also contributes to faster and more accurate decision-making. However, obstacles such as high costs, lack of infrastructure accessibility, and lack of skills and understanding of ICT remain major barriers to its use by shoe crafters there. Therefore, the role of the government and relevant institutions is crucial in providing support and facilitation to ensure that shoe crafters can utilize ICT optimally to improve their business performance and competitiveness. This research contributes to the development of understanding regarding the utilization of ICT by shoe crafters in Cibaduyut, especially, and SMEs in Indonesia in general. In conclusion, the use of ICT by shoe crafters in Cibaduyut has improved their productivity in business. The Bandung city government should facilitate shoe crafters by improving infrastructure and policies that support their sustainable business